Dynamic interactions of luteinizing hormone receptors during signal transduction - Lei, Ying, author; Roess, Deborah A., advisor; Barisas, B. G., committee member; Graham, James K., committee member; Fox, Michael H., committee member (Colorado State University. Libraries, 2005)
There is increasing evidence that receptor-mediated signal transduction by G-protein coupled receptors can involve self-association and redistribution of plasma membrane receptors into specialized plasma microdomains or rafts. These membrane fragments are characterized by insolubility in cold Triton X-100 and localization to low density regions in sucrose gradients. Here, we characterized the translocation of wild type rat and human luteinizing hormone (LH) receptors into rafts following the binding of human chorionic gonadotropin (hCG) via a sucrose gradient ultracentrifugation method. We have also examined constitutively active human LH receptors which, in contrast to wild type receptors, were self-associated in the absence of hormone with a significant fraction of the receptors localized in rafts. Receptor localization in membrane rafts did not occur when cells were pretreated with 1% methyl-(β-cyclodextrin (MβCD), a cholesterol sequestering agent that reduces membrane cholesterol and disrupts membrane rafts. Pretreatment of cells with MβCD also significantly decreased levels of hormone-induced intracellular cAMP in wild type LHR, but not constitutively active receptors, and reduced the extent of receptor self-association as evaluated by fluorescence resonance energy transfer (FRET). Translocation of LH receptors into rafts required a functional hormone-receptor complex. When CHO cells expressing FLAG-LHR-wt were treated with an hCG antagonist such as deglycosylated hCG, receptors remained in high density membrane fractions as did hCG-treated point mutated receptor LHR-K583R that has reduced responsiveness to hCG binding. On the other hand, extensive crosslinking of wild type LH receptors with anti-FLAG antibody and a second anti-mouse IgG, while elevating intracellular cAMP, did not drive LH receptors into the raft environment. Finally, we found that the LH receptor C-terminus and its ability to be palmitoylated might affect raft localization. In conclusion, translocation of the LH receptor into specialized membrane microdomains may be important in hormone-mediated signaling and a characteristic of functional, hormone-occupied LH receptors. Nonetheless, under some conditions, the raft environment is not essential for cAMP-mediated signaling.
Keywords: cellular biology; molecular biology